Quest intro : - Blass, Laurie (McGraw-Hill, 2007)
Quest Second Edition parallels and accelerates the process native-speaking students go through when they prepare for success in a variety of academic subjects. Quest helps students get "up to speed" in terms of both academic content and language skills.. Each student book unit focuses on a different area of university study anthropology, art, biology, business, ecology, economics, history, literature, psychology, and sociology..